REVOLUTION AND CIVIL WAR IN CENTRAL AMERICA: TWO CONCEPTS IN THE POLITICAL THOUGHT OF FRANCISCO MORAZÁN - Gómez Murillo, Vicente (2018)
The Central American Independence and the project of a Central American Republic in the first decades of the 19th Century are often portrayed, along with the rest of the Spanish American Revolutions, as a deviation from an original model of revolution based on the French and North American experiences. The purpose of this paper is to analyze the concepts of revolution and civil war in the political thought of Francisco Morazán, champion of the Central American unity, to contribute to rethink the interpretation of Latin American history as a deviation. As for the methodological approach, the choice is for the conceptual history of Reinhart Koselleck and a proper historical contextualization. Together, these tools will help to show how the Central American political process had its own characteristics, which the historical actors were aware of and from which they thought their experience as part of the major global transformations of the Age of Revolutions.